SELECTION BEST ELEMENTARY SCHOOL IN SEI DADAP USING SAW METHOD - Putri Vina Bancin; Iqbal Kamil Siregar; Cecep Maulana (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: One of the main aspects of education, such as elementary school education, the initial stage for children to continue to the next level of education. Elementary school for the first level of education plays an important role in developing students' attitudes, skills, and interests and talents. Every new academic year, students and parents will choose the best school according to their wishes. There are many choices of schools with a variety of different offerings provided. That way, many parents of students are confused by the many choices of types of schools for their children. This study aims to provide recommendations for the best elementary schools in the Sei Dadap sub-district based on the criteria desired by prospective students by applying the Simple Addictive Weighting (SAW) method to a system The SAW method helps in solving simple unstructured problems so that by applying the SAW method a more effective decision-making process can be carried out. The data used as alternative data are elementary schools in the Sei Dadap sub-district. The criteria used in decision making include accreditation, facilities, extracurricular activities, number of classrooms, number of students, and distance between schools. Keywords: Decision Support System; Elementary school; Simple Addictive Weighting Abstrak: Salah satu aspek pendidikan utama seperti pendidikan sekolah dasar yang tahap awal bagi anak untuk melanjutkan ke jenjang pendidikan berikutnya. Sekolah Dasar jenjang pendidikan pertama memegang peranan penting dalam mengembangkan sikap, keterampilan, serta minat dan bakat siswa. Setiap tahun ajaran baru, siswa dan orang tua akan memilih sekolah terbaik sesuai dengan keinginan mereka. Ada banyak pilihan sekolah dengan beragam penawaran berbeda yang disediakan. Dengan begitu, banyak orang tua siswa yang bingung dengan banyaknya pilihan jenis sekolah untuk anaknya. Penelitian ini bertujuan untuk memberikan rekomendasi sekolah dasar terbaik di kecamatan Sei Dadap berdasarkan kriteria yang diinginkan oleh calon siswa dengan menerapkan metode Simple Addictive Weighting (SAW) pada suatu sistem. Metode SAW membantu dalam menyelesaikan masalah sederhana yang tidak terstruktur sehingga dengan menerapkan metode SAW dapat dilakukan proses pengambilan keputusan yang lebih efektif. Data yang digunakan sebagai data alternatif adalah sekolah dasar yang ada di kecamatan Sei Dadap. Kriteria yang digunakan dalam pengambilan keputusan meliputi akreditasi, fasilitas, kegiatan ekstrakurikuler, jumlah ruang kelas, jumlah siswa, dan jarak antar sekolah. Kata kunci: Sistem Pendukung Keputusan; Simple Addictive Weighting; Sekolah Dasar